(untitled) (Revista de Artes Marciales Asiáticas, 2019)
In this panel, five experts present their personal experiences in martial arts and combat sports (MA&CS) research. These experiences represent the two classic approaches to our studies: the quantitative and the qualitative. Above all, the panel aims to foster debate and reflection on the complementarity of these methods when trying to embrace the complexity of MA&CS.